Twisted Aspirin Crystals - Cui, X.; Rohl, Andrew; Shtukenberg, A.; Kahr, B. (The American Chemical Society, 2013)
Banded spherulites of aspirin have been crystallized from the melt in the presence of salicylic acid either generated from aspirin decomposition or added deliberately (2.6–35.9 mol %). Scanning electron microscopy, X-ray diffraction analysis, and optical polarimetry show that the spherulites are composed of helicoidal crystallites twisted along the <010> growth directions. Mueller matrix imaging reveals radial oscillations in not only linear birefringence, but also circular birefringence, whose origin is explained through slight (~1.3°) but systematic splaying of individual lamellae in the film. Strain associated with the replacement of aspirin molecules by salicylic acid molecules in the crystal structure is computed to be large enough to work as the driving force for the twisting of crystallites.